FIQIH EMANSIPATORIS (Membangun Metodologi Fiqih Pembebasan Bagi Perempuan) - Muhammad Ngizzul Muttaqin; Miftah Rosadi; Arif Nur'aini (Raheema, 2021)
Labeling women who only do homework seems in the current modern context cannot be pinned on. Important positions held by women in the public sphere today seem to have broken the chain of women as workers in the private sphere. In the realm of classical Islamic law (fiqh) studies also provide justification for women as workers in the private world. So that the construction of classical Islamic law (fiqih) seems no longer relevant to use in today’s modern world, where women have an important position in social activities and as effort to provide equal opportunities and rights for all humans. As a literature-based study and literature study, this paper tries to reveal the mismatch of the use of classical Islamic law (fiqh) about women in the modern era today. The findings in this show that realizing emancipatory Islamic law (fiqh) is a necessity in order to realize Islamic law (fiqh) that is relevant to the social life of today’s society. So that the ideals of Islamic law (fiqh) which are righteous sholih fi kully al-zaman wa al-makan can be realized.